PEMANFAATAN SISTEM PENGERING MENGGUNAKAN MIKROKONTROLERGENUINO UNO DAN SOLAR SELUNTUK PENGOLAHAN HASIL PERTANIAN MASYAKARAKAT DESA PASAR PEDATI DAN DESA HARAPAN - Anizar Indriani; Eng Hendra; Yovan Witanto (DHARMA RAFLESIA, 2018)
The daily life of the people in Pasar Pedati Village and Harapan Village, Central Bengkulu Regency, especially the housewives is processing agricultural products such as cassava, copra, and banana.Cassava is made into cassava chips and rengginang. This devotional activity aims to transfer technology and science in processing agricultural products and help villagers to create versatile dryers.This versatile drying machine works by utilizing solar and heat energy absorbed by copper plates where the heat is insulated using a glass layer.Heat utilization is made by copper plate so it must be made with transparent glass design on the top and around the wall of the dryer.The frame of the glass stand is made of aluminum and is assembled using a rivet.The process of choosing and making of this drying machine involves the people of Pasar Pedati Village and Harapan Village, both men and women. Most of the men in Pasar Pedati Village work on farming and also work outside the village, so that during the day there are housewives working on the process of drying their crops.With this versatile drying machine training, Pasar Pedati and Desa Harapan villagers are particularly enthusiastic in training. Because these dryers are very helpful for them in processing the crops better, cleaner, and the time is not too long.Drying process with this drying machine also does not require a large area. Drying cassava made into cassava chips and rengginang takes about 2-3 hours, compared to manual drying done by drying the open yard takes 12-16 hours.The society can make this tool itself in order to increase their income.Keywords: dryer machine, cassava, aluminum copra, solar cell